2016
DOI: 10.1161/circheartfailure.116.003123
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure With Improved Ejection Fraction: Clinical Characteristics, Correlates of Recovery, and Survival

Abstract: Background— Heart failure with recovered or improved ejection fraction (HFiEF) has been proposed as a new category of HF. Whether HFiEF is clinically distinct from HF with persistently reduced ejection fraction remains to be validated. Methods and Results— Of the 5010 subjects enrolled in the Valsartan Heart Failure Trial (Val-HeFT), 3519 had a baseline left ventricular EF of <35% and a follow-up echocardiographic assessment of EF at 12 months. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
104
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 24 publications
13
104
1
2
Order By: Relevance
“…27 Finally, in the subset of patients with repeat echocardiography imaging in the Valsartan Heart Failure Trial (Val-HeFT), 321 of 3519 (9.1%) patients with initial LVEF <35% (including ischemic aetiologies) improved LVEF to >40% at 1-year follow up, and recovery was associated with improved survival at 2-year short-term follow up (log-rank p -value comparing survival in group with improved LVEF compared to group without improved LVEF = 0.005). 28 …”
Section: Prognostic Implications Of LV Remodelingmentioning
confidence: 99%
“…27 Finally, in the subset of patients with repeat echocardiography imaging in the Valsartan Heart Failure Trial (Val-HeFT), 321 of 3519 (9.1%) patients with initial LVEF <35% (including ischemic aetiologies) improved LVEF to >40% at 1-year follow up, and recovery was associated with improved survival at 2-year short-term follow up (log-rank p -value comparing survival in group with improved LVEF compared to group without improved LVEF = 0.005). 28 …”
Section: Prognostic Implications Of LV Remodelingmentioning
confidence: 99%
“…Although statistically significant, it is debatable whether this slight increase in LVEF is clinically relevant or whether it can explain the symptomatic improvement in these patients. Nevertheless, many studies have found a survival benefit in patients with HFrEF whose LVEF improved after treatment for HF . Some of these studies found a very significant increase in LVEF .…”
Section: Echocardiography In Anemia and Iron Deficiencymentioning
confidence: 99%
“…Nevertheless, many studies have found a survival benefit in patients with HFrEF whose LVEF improved after treatment for HF. [66][67][68][69][70] Some of these studies found a very significant increase in LVEF. [66][67][68]70 However, any statistically significant improvement in LVEF may be associated with improved survival, independently of the baseline LVEF or the magnitude of the increase.…”
Section: Systolic Functionmentioning
confidence: 99%
“…In this issue of Circulation: Heart Failure, Florea et al 11 used data from the Valsartan Heart Failure Trial (Val-HeFT) to identify a subset of patients who entered the study with a reduced LVEF of <35% but went onto improve their ejection fraction (HFiEF) to >40% after 12 months of follow-up. They specifically sought to better characterize this improved LVEF population, determine independent predictors of improvement, and compare prognosis to patients who did not improve.…”
Section: See Article By Florea Et Almentioning
confidence: 99%